Identification, cloning, and characterization of the Escherichia coli sohA gene, a suppressor of the htrA (degP) null phenotype. - Baird, L (1990)
Two extragenic suppressors which allow temperature-sensitive htrA mutant Escherichia coli bacteria to grow at 42 degrees C and simultaneously acquire a cold-sensitive phenotype at 30 degrees C were isolated. The cold-sensitive phenotype exhibited by one of the mutants was used to clone the corresponding wild-type copy of the suppressor gene. This was done through complementation with a mini-mu plasmid E. coli DNA library, by selection for colonies which were no longer cold sensitive, at 30 degrees C. The cloned suppressor gene was shown to complement the cold-sensitive phenotype of both suppressor mutations. It was mapped to 68 min on the E. coli chromosome through hybridization to the Kohara library of overlapping lambda transducing bacteriophages, which covers the entire E. coli chromosome. The complementing gene was further subcloned on an 830-base-pair (bp) DNA fragment. DNA sequencing revealed the presence of an open reading frame (ORF) of 333 bp which could encode a protein of 12,359 Mr. Subcloning of various DNA fragments from within this 830-bp DNA fragment suggests that this ORF is most likely responsible for suppression of the cold-sensitive phenotype of the htrA suppressor bacteria. By using a T7 polymerase system to overproduce plasmid-encoded proteins, a protein of approximately 12,000 Mr was produced by this cloned DNA fragment. This ORF defines a previously undiscovered gene in E. coli, called sohA (suppressor of htrA).